New, north-easternmost locality for Bembidion monticola Sturm, 1825 (Coleoptera: Carabidae) in Europe: relict of ancient distribution or a result of range expansion? - Kovalenko, Yakov; Telnov, Dmitry (Entomologica Fennica, 2018)
A new record of a subpopulation of Bembidion monticola Sturm, 1825 from Arkhangelsk region (Northern Europe, Russia) is discussed. The locality of this record is remote, about 700 km to the east from the northernmost previously known locality of this species. Ecology and distribution of B. monticola in northern Europe are reviewed, as well as possible ways of its spread further to northeast are hypothesised.